Optimalisasi Kandungan Lemak dan Serat Pangan pada Snack Bar Berbasis Tempe dan Kacang Merah: Sumber Energi Tinggi untuk Atlet - Wahida, Difia Addini Nur; Kurnia, Pramudya; Mustikaningrum, Fitriana (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Due to the intensity of physical activity performed, athletes have higher energy and nutrient requirements than the general public. Snack bars are one option to help athletes meet their high energy needs. This Snack bar is made from main ingredients such as tempeh, red beans, crispy rice, and honey. This study aims to identify the content of dietary fiber and fat in snack bars made from tempeh and red beans. The experimental study was conducted using three formulations of snack bars, namely formulation a: tempe 34.69%: red beans 26.53% (tempe 85 g, red beans 65 g, rice crispy 25 g), formulation B: tempe 30.61%: red beans 30.61% (tempe 75 g, red beans 75 g, rice crispy 25 g), formulation C: tempe 26.53%: red beans 34.69% (tempe 65 g, red beans 85 g, crispy rice 25 g). The results of this study the highest fat content in the snack bar substitution of tempeh and red beans is formula A with a yield of 13.37% and the highest total dietary fiber content in formula C with a yield of 7.09%. There is an effect of tempe and red bean substitution on fat content with one Way ANOVA test results p=0.000. The effect of tempe and red bean substitution on total dietary fiber content with one Way ANOVA test value p=0.000. The highest fat content is formula A with a yield of 13.37% and the highest dietary fiber content in formula C with a yield of 7.09%.